Poverty impacts of food price shocks and policies - Laborde Debucquet, David; Lakatos, Csilla; Martin, Will (World Bank, 2019)
In the event of large swings in world food prices, countries often intervene to dampen the impact of international food price spikes on domestic prices and lessen the burden of adjustment on vulnerable population groups. Although individual countries can succeed in insulating their domestic markets from short-term fluctuations in global food prices, the collective intervention of many countries exacerbates the volatility of world prices. Insulating policies introduced during the 2010-11 food price spike accounted for 40 percent of the increase in the world price of wheat and 25 percent of the increase in the world price of maize. Combined with government policy responses, the 2010-11 food price spike increased global poverty by 1 percent or 8.3 million people.